Pengaruh Profitabilitas, Likuiditas Dan Penilaian Pasar Terhadap Return Saham (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di BEI Periode 2017-2019) - Laras Noviyanti; Ronny Malavia Mardani; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the effect of profitability ratios, liquidity ratios and market valuation ratios, each of which is proxied sequentially by partial return on equity, current ratio, and price to book value on stock returns of manufacturing companies listed on the Indonesia Stock Exchange. The research period used is 3 years, namely the 2017-2019 period.This research design is explanative. The research population includes all food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The sampling technique used was purposive sampling technique. Based on the predetermined criteria, a total sample of 14 companies was obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange. Multiple linear regression analysis method.The results of this study indicate that the projected profitability with return on equity (ROE) has a positive and significant effect on stock returns, the projected liquidity with the current ratio (CR) has a negative and insignificant effect on stock returns, the projected market valuation with price to book value(PBV) has a negative and significant effect on stock returns. Keywords: Profitability, Liquidity, Market Valuation, Stock Return